2021
DOI: 10.3390/sym13071180
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bi-Additive Mappings and Bi-Jensen Mappings

Abstract: Symmetry is repetitive self-similarity. We proved the stability problem by replicating the well-known Cauchy equation and the well-known Jensen equation into two variables. In this paper, we proved the Hyers-Ulam stability of the bi-additive functional equation f(x+y,z+w)=f(x,z)+f(y,w) and the bi-Jensen functional equation 4fx+y2,z+w2=f(x,z)+f(x,w)+f(y,z)+f(y,w).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Alanazi et al [22] examined the fuzzy stability of a finite variable additive FE using direct and fixed point approaches. Bae et al [23] demonstrated the stability problem and proposed a theory that symmetry is repeated self-similarity by simulating the well-known Cauchy and Jensen equations in two variables. Turab et al [24] studied the applications of Banach limit in UHS.…”
Section: Introductionmentioning
confidence: 99%
“…Alanazi et al [22] examined the fuzzy stability of a finite variable additive FE using direct and fixed point approaches. Bae et al [23] demonstrated the stability problem and proposed a theory that symmetry is repeated self-similarity by simulating the well-known Cauchy and Jensen equations in two variables. Turab et al [24] studied the applications of Banach limit in UHS.…”
Section: Introductionmentioning
confidence: 99%